Rendo Bangku Craft of Koto Gadang West Sumatra on Fashion Products - Ranelis Ranelis; Rahmad Washinton; Kendall Malik; Mira Utami (Mudra Jurnal Seni Budaya, 2023)
This article entitled “Rendo Bangku Craft of Koto Gadang West Sumatra on Fashion Products” aims to raise the potential of Koto Gadang’s rendo bangku patterns, as one of the excellent products of the Koto Gadang village community. Rendo bangku craft which was originally used to decorate the edges of women's shawls in Koto Gadang is now being innovated by placing Koto Gadang’s rendo (embroidery) on fashion products. The method used is experimental, by the means of exploration, design, manifestation, and evaluation. Exploration was carried out to find ideas or concepts related to the product of Koto Gadang local embroidery which was carried out using observation, literature study, and interviews. Designing is the step of an embodiment of ideas and concepts from exploration into the design of women’s wear, men’s wear, and accessories. Embodiment is the step to manifest the result of the pattern design of fashion products in a real form into working drawings, as well as into finished products including men's clothing.